A Research-Informed Training Course for Interlingual Respeaking - Dawson, Hayley (Journal of Audiovisual Translation, 2020)
As audiovisual material is increasingly and globally streamed live, there is a growing demand for this live content to be made accessible in a foreign language. This calls for interlingual live subtitling, which is intended for both foreign-language and hearing-impaired viewers, illustrating the wide and inclusive notion of Media Accessibility (MA) where access is needed for audiences with and without disabilities (Romero-Fresco, 2018). This paper begins with an overview of interlingual respeaking including research, demand and training. Empirical results of interlingual respeaking experiments are presented with an emphasis on the task-specific skills required, which have been validated through experimental research. Then, a research-informed training model for interlingual respeaking is presented that acts as a framework upon which to base the proposal of a training course. This is regarded as an essential step to help consolidate interlingual respeaking as a viable access service and to produce quality live subtitles to benefit a wide audience.